PERAMALAN PERMINTAAN KOMODITI PAPRIKA (CAPSICUM ANNUM) DI PT BIMANDIRI AGRO SEDAYA, LEMBANG - Puji Rahmawati Nurcahyani; Tania Fauzia Iqbal (AGROINTEK, 2014)
PT Bimandiri Agro Sedaya is a non- manufacturing company ( services ) which operate in the field of trade as a supplier of fresh vegetables to retail. In December 2013, the fulfillment of the demand of red paprika, yellow paprika dan green paprika are 70,09 %; 70,24 %, 73,95 % respectively, so we need a method of accurately forecasting demand to estimate the demand of paprika early. The data is demand of red, yellow and green paprika commodities during September to December 2013. The results of pattern data analysis by least squares method and autocorrelation function shows that data have stationery pattern so used moving average method, single exponential smoothing and ARIMA. The result of MSE shows ARIMA metohd has the lowest MSE value for whole paprika. ARIMA method for red paprika, yellow paprika and green paprika are ARIMA (1,1,2) with MSE of 434,7;ARIMA (2,1,3) with MSE of 164,4 and ARIMA (1,0,1) with MSE of 321,9 respectively